2013
DOI: 10.1111/mec.12341
|View full text |Cite
|
Sign up to set email alerts
|

Combined analyses of kinship and FST suggest potential drivers of chaotic genetic patchiness in high gene‐flow populations

Abstract: We combine kinship estimates with traditional F-statistics to explain contemporary drivers of population genetic differentiation despite high gene flow. We investigate range-wide population genetic structure of the California spiny (or red rock) lobster (Panulirus interruptus) and find slight, but significant global population differentiation in mtDNA (ΦST = 0.006, P = 0.001; Dest_Chao = 0.025) and seven nuclear microsatellites (FST = 0.004, P < 0.001; Dest_Chao = 0.03), despite the species’ 240- to 330-day pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
152
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 143 publications
(170 citation statements)
references
References 164 publications
(281 reference statements)
12
152
0
Order By: Relevance
“…Most parentage studies have used fishes, although an expansion of using parentage and kinship relationships comes from a recent study on California spiny lobsters, Panulirus interruptus, which require 240-330 d of pelagic development prior to settlement. Despite high gene flow and extensive mixing, Iacchei et al (2013) showed specific populations, associated with upwelling fronts, contained significantly more kin than expected and were thus significantly differentiated from other sites throughout the species range.…”
Section: Spatial Planning and Restorationmentioning
confidence: 99%
“…Most parentage studies have used fishes, although an expansion of using parentage and kinship relationships comes from a recent study on California spiny lobsters, Panulirus interruptus, which require 240-330 d of pelagic development prior to settlement. Despite high gene flow and extensive mixing, Iacchei et al (2013) showed specific populations, associated with upwelling fronts, contained significantly more kin than expected and were thus significantly differentiated from other sites throughout the species range.…”
Section: Spatial Planning and Restorationmentioning
confidence: 99%
“…This 'isolation by resistance' (IBR) pattern may be particularly evident when an organism's reproductive strategy involves a sedentary adult phase and a pelagic larval stage that is subject to prevailing currents. Complex ocean circulation can represent significant barriers to dispersal and can produce patterns of genetic structure that are often difficult to interpret; however, incorporating oceanographic mechanisms into the analyses of population genetic data has placed confounding patterns of genetic patchiness into more ecologically relevant contexts [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, even if selection occurs during the planktonic stage (Johnson & Black 1984), genetic drift is thought to be the main force shaping genetic structuring among groups of settlers, sometimes promoting increased relatedness among individuals (e.g. Larson & Julian 1999, Planes & Lenfant 2002, Selkoe et al 2006, Iacchei et al 2013, Aglieri et al 2014, review in Hauser & Carvalho 2008. This phenomenon, called sweepstake recruitment, has been widely documented (Hellberg 2006, 2009, Selkoe et al 2008, Hedgecock & Pudovkin 2011.…”
Section: Introductionmentioning
confidence: 99%